The Impact of European Union Funds on The GDP Of the Republic of Croatia: An Overview by Counties... - Anđela PEROVIĆ; Jurica BOSNA; Dario VIŠTICA (Communications of International Proceedings, 2022)
The European Union, through various assistance programs, seeks to improve the development of all its parts. The availability of funding from European funds aims to reduce regional disparities between EU member states, improve the living standards of citizens, living conditions and reduce poverty and wealth disparities. The overall impact of EU funds depends on the funding structure and absorption capacity of the country. The project of the European Union is unique and equally complex. Many former socialist countries, including Croatia, decided to join the EU because they felt they had more benefits than costs. One of the reasons for such thinking was the redistribution of wealth through EU funds. Although the funds are available, the money still needs to be focussed to develop projects quintessential for use of all possible resources. The task of the Republic of Croatia is to take advantage of the funds of the European Union. The aim of this paper is to determine how successfully the Republic of Croatia has used available funds, namely to show the allocation and use of withdrawn funds at the national and regional level, specifically by counties and to analyse the relationship between the withdrawal of the EU funds and county GDP.
Keywords: EU funds; Economy of the Republic of Croatia; Counties of the Republic of Croatia; GDP.